KEWENANGAN PEMERINTAH DALAM PEMBENTUKAN PERATURAN KEBIJAKAN - Astariyani, Ni Luh Gede (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015), 2015)
Shifting the notion countries formal law into state law meteriil (wefare staat) within the meaning of the welfare state agency or official  Administrative often take a variety of specific policy measures, among others, creating what is commonly called policy rule(beleidsregel). Such products can not be separated from the association Freies  ermessen. In order setting is a rule or rules of conduct set that regulation (Regeling) can be found in the legislation (Algemeen verbindende voorschriften) internal rules that apply to the (interne regelingen) and policy (beleidrege). Establishing the policy rule (beleidsregel) is located on the beoordelingsruimte (space considerations) given by the legislators to officials or governing bodies to take action on its own initiative public law that is setting, determination and positive action to resolve the problem- governance problems faced. Freis ermessen only intended use in the public interest. Freis ernessen implementation should be morally accountable to God Almighty, uphold the dignity and the degree of human dignity and the values ??of truth and justice, promoting unity and oneness, for the sake of joint / public interest. Tests on policy rule is more geared to doelmatigheid guided by the general principles of good governance
Keywords: Authority; Policy Rule